A near-infrared light-responsive extracellular vesicle as a "Trojan horse" for tumor deep penetration and imaging-guided therapy. (February 2021) - Xu, Zeng; Huang, Huabei; Xiong, Xiang; Wei, Xiaoqing; Guo, Xing; Zhao, Jingya; Zhou, Shaobing
Abstract: How to make the nanoparticles evade immune surveillance and deeply penetrate the tumor tissues is of great importance to maximize the therapeutic efficacy of nanomedicines. Here, a near-infrared (NIR) light-responsive extracellular vesicle as a nanoplatform is developed to realize long circulation in blood, deep penetration in tumor tissues and rapid body elimination after the treatment. Like a "Trojan horse", the nanoplatform is obtained by hiding the anti-tumor soldiers (DOX and 4.2 nm Ag2 S quantum dots (QDs)) into the macrophage cell-secreted vesicle through electroporation. The natural composition and tumor targeting activity of the extracellular vesicles enable the nanoplatform to achieve a high accumulation in tumor and the in vivo biodistribution can be monitored by NIR fluorescence imaging of the Ag2 S QDs. After the nanomedicines accumulate at the tumor sites, the soldiers will be released from the "Trojan horse" by utilizing the NIR photothermal effect of the Ag2 S QDs. The released ultrasmall QDs and DOX can penetrate the whole tumor with a diameter of about 9 mm and effectively kill the tumor cells. Moreover, the inorganic QDs can be rapidly excreted from the body through renal clearance after the treatment to avoid the potential toxicity.